Pelatihan kelompok Guru Bahasa Inggris di Kota Makassar - Mardiani Mardiani; Syamsuddin Syamsuddin; Kartina Kartina (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
The purpose of this study is to solve the problemfaced by English teachers in Makassar in improving theirknowledge and skill in teaching through communicativegrammar teaching training. This training involves Englishteachers in Makassar private junior high schools. They aretrained by experts from university and language centre who arealso the experienced trainers. This training held in 16 meetingsat British Course Makassar. The result of this training showsthat 1) the English teachers able to implement the TeachingGrammar Communicatively learning model, 2) the learningmodule of Teaching Grammar Communicatively is feasible forother junior high schools, 3) the participation level of theteachers in this training is high viewed from their attendanceand being active in doing their tasks.